2010
DOI: 10.1007/s11094-010-0425-6
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of imidazole derivatives: dacarbazine and the new alkylating agent imidazene (Review)

Abstract: The physicochemical properties and antitumor activity of dacarbazine, its analogs, and the new alkylating agent imidazene are reviewed. It is shown that the activity of dacarbazine is superior to most of its analogs. Imidazene exhibits an advantage over dacarbazine with respect to both stability and activity and can be used for the treatment of malignant melanoma and sarcoma of soft tissues and in combined chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Further, the literature indicated that some review papers on related topics have appeared on imidazoles. [54][55][56][57] However, none of the articles discussed the classes of imidazoles as anticancer agents based on the mode of action, and a review has not appeared since 2010. Therefore, an updated review of the recent advances in this field is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the literature indicated that some review papers on related topics have appeared on imidazoles. [54][55][56][57] However, none of the articles discussed the classes of imidazoles as anticancer agents based on the mode of action, and a review has not appeared since 2010. Therefore, an updated review of the recent advances in this field is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Various oxygen-containing azoles, as exemplified by oxadiazoles, oxazoles, and isoxazoles, have been also thoroughly studied for their diversified biological activities. Widely used as potent antifungal agents (fungicides) due to their valuable properties like broad spectrum of action, chemical stability, and oral bioavailability [39][40][41][42], various azole derivatives have also demonstrated many other promising biological properties including antidiabetic, immunosuppressant, antiinflammatory, antiviral, antitubercular, and anticancer activities [8,12,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of their studies and applications, major advances in the chemistry of pyrazoles, imidazoles, triazoles, tetrazoles, and their fused heterocyclic derivatives have been performed [2][3][4][5][6]. These azoles are also widely found as core structures in a large variety of natural and artificially synthesized compounds possessing important agrochemical and pharmaceutical properties [7][8][9][10][11]. The well-known ability of these heterocyclic cores to serve both as biomimetics and reactive pharmacophores encourages their applications in numerous drugs [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Among them, imidazolo‐indole framework has received growing attentions in recent years because of its fused heterocyclic skeleton involved in a large number of natural products and as drug candidate. [ 2 ] Several of their synthetic analogues have many biological properties, that is, antiinflamatory, [ 3 ] antimicrobial, [ 4 ] anticancer, [ 5 ] antitubercular, [ 6 ] antidengue, [ 7 ] anti‐analgesic, [ 8 ] anthelmintic, [ 9 ] antimycotic, [ 10 ] antitumor, [ 11 ] and antibacterial activities. [ 12 ] Also, the imidazole nucleus has displayed an important role in some advanced technology fields such as biological imaging, [ 13 ] glucagon receptors, [ 14 ] fluorescence labeling agents, [ 15 ] modulators of P‐glycoprotein (P‐gp)‐mediated multidrug resistance (MDR), [ 16 ] and chromophores for nonlinear optic systems (NLOS).…”
Section: Introductionmentioning
confidence: 99%